Is Druidry Indigenous? The Politics of Pagan Indigeneity Discourse. (16th November 2018) - Owen, Suzanne
Abstract : This article asks if "indigenous, " associated as it is with "colonized peoples, " is being employed strategically by Druids in Britain to support cultural or political aims. Prominent Druids make various claims to indigeneity, presenting Druidry as the pre-Christian religion of the British Isles and emphasizing that it originated there. By "religion" it also assumes Druidry was a culture equal to if not superior to Christianity—similar to views of antiquarians in earlier centuries who idealized a pre-Christian British culture as equal to that of ancient Greece. Although British Druids refute the nationalist tag, and make efforts to root out those tendencies, it can be argued that it is a love of the land rather than the country per se that drives indigeneity discourses in British Druidry.